Call for papers - Algebraic practice in classrooms and beyond - Kilhamn, Cecilia (NOMAD Nordic Studies in Mathematics Education, 2024)
To meet the needs of the 21st century societies it is necessary to change the nature of algebra teaching. Challenges such as climate change and pandemics require understanding of patterns of growth and change of complex systems, and engaging in public discourse about these challenges requires the ability to argue in general terms about abstract quantities. Algebra is the area of mathematics focusing on generalization, but for many people, school algebra consists of rearranging strings of symbols qccording to rules, without developing the ability to reason with generalizations. There is a need for approaches to algebra learning and teaching that develop the ability to use generalizations to describe, analyze and solve problems in real life, as well as within mathematics, an ability we call ”algebraic practice”.